Commemorative events memory, identities, conflict - Frost, Warwick; Laing, Jennifer (London Routledge, 2013)
"This is the first book to provide an in - depth critical examination of commemorative events, particularly what they mean to societies and how they are used by governments as well as impacts on other stakeholders. The book fully explores these issues by reviewing all the major types of commemorative events including, nationhood or independence, wars, battles, famous people and cultural milestones from varying geographical regions and stakeholder perspectives. By doing so the book furthers understanding of these types of events in society as well as furthering knowledge of social and political uses and impacts of events."--Provided by publisher.
Keywords: Special events; Anniversaries; Memorials